Team diversity - van Knippenberg, Daan (Henry Stewart Talks, 2014)
Why diversity?, Types of diversity, The challenge, Informational resource perspective, Social categorization perspective, Integration: categorization-elaboration model, Contingencies of elaboration, Contingencies of intergroup bias, Contingencies of social categorization, Managing diversity: team design, Managing diversity: team development